JENIS MINERAL LIAT DAN PERUBAHAN SIFAT KIMIA TANAH AKIBAT PROSES REDUKSI DAN OKSIDASI PADA LINGKUNGAN TANAH SULFAT MASAM - Yuliana, E. Dewi (Bumi Lestari, 2012)
This research was performed to study the characteristic of acid sulphate  agricultural soil. Since “pasang surut” area are very potensial to be used for agriculture, it advantages and disadvantages has to be investigated based on mineral exchange and chemical characteristic due to oxidation and reduction processes. This research was using completely randomized design ; soil was collected from agricultural area using pots before these pots were then randomly mounted in glass house. This soil then analysed in Laboratory to find out its characteristics such as clay mineral and chemical characteristics of the soil. These analysis were performed twice, i.e. before reduction-oxidation and after reduction-oxidation process. Data than statistically analysed in semi quantitative and qualitative before descriptive interpretations. Results from this analysis indicated that; (1) Reduction-oxidation processes applied to the acid sulfat soil do not change the kind of mineral contained in the soil whether montmorilonit, illit, kaolinit, goethit, or quart; (2) Soil being reduce for 2 months underwent chemical changes such as, soil pH increased form 5 to 5.30, al-dd content were decreased from 7.81 me/100g into 5.35 me/100g, iron ferro was increased from 41.14 ppm into 284.32 ppm, but ferric iron was decreased from 424.73 ppm into 185.79 ppm, the amount of soluble sulphate was decreased from 436.18 ppm into 240.74 ppm; (3) After it was oxidized for two months, chemical characteristic of the soil was changed, soil pH was changed from 5.00 into 4.26, Al-dd was increased from 7.81 me/100g into 20.42 me/100g, ferro iron content was decreased from 51.14 ppm into 21.59 ppm, by contrast, ferric iron content was increased from 424.73 ppm into 448.52 ppm, soluble sulphate was increased from 384.64 ppm into 436.18 ppm.
Keywords: clay mineral; chemical characteristic soil; acid sulphate soil envirovement; reduction and oxidation